Effectivity of Law Number 21 Of 2007 In Esnaring Pimps as Sex Commercial Services Procuress - Winda Fathia Pilili (Faculty of Law, University of Mataram, 2021)
In the modern era, prostitution metamorphose into the branch of industry which in line with the pornography or striptease. For Indonesian people, prostitution have been understood as work, in which exchange intercourse with money or prizes, the same with services purchase or trade. Yogyakarta which known as education city is not spared either with prostitution. Cited by Tribun Jogja, revealed that cases of human trafficking that covered by prostitution in Sleman, Yogyakarta. It was occurred in three different locations, are Pasar Kembang, Bong Suwun and Giwangan. This work aims were to know and to analyze how criminal law in Indonesia regulated pimp as procuress of sex commercial agent in Yogyakarta and its law enforcement mechanism. Laws related of pimp regulated in the Article 290 and 560 Indonesia Criminal Code. Meanwhile, in Yogyakarta there is a regulation which prohibit the public prohibition i.e. Local Regulation Number 18 of 1954. Law enforcement mechanism towards prostitution by implement the Law Number 21 of 2007 in punishing pimps in Yogyakarta, with strong commitment to eradicate this crime. This work is empirical legal research which applied juridical and empirical approaches in Yogyakarta by taking data in Local Police Office of Yogyakarta.